Atomization gas type, device configuration and storage conditions strongly influence survival of Lactobacillus casei after spray drying. Issue 3 (1st February 2022) - Jokicevic, Katarina; Lebeer, Sarah; Kiekens, Filip
Abstract: Many pathologies are characterized by an imbalance between the beneficial bacteria and potentially pathogenic microbes, i.e., dysregulated host/microbial interactions. Probiotic bacteria are increasingly explored for regulation of immune responses and restoring this imbalance. The application of probiotics most commonly involves drying in formulation development, that can potentially reduce their viability and functionality, hence different protective strategies are needed. Here, spray drying was used for probiotic preservation and effects of device configuration, oxygen injury and encapsulation with increasing skim milk concentrations, were studied on the survival of L. casei AMBR2. Quantitative analysis showed no significant differences on bacterial viability for spray drying in an open versus closed system whilst spray drying in a co-current gas flow. Addition of the anti-oxidant, ascorbic acid, to the drying medium adversely impacted viability. Also, no benefits of nitrogen spray drying were observed, implying that oxygen-induced damage is not significant in this setup, at least for the specific tested strain. Additionally, this work shows how storage conditions and total feed solid content significantly alter spray drying viability outcomes. Spray drying was able to retain the high viability of cells of 10 9 CFU/g and higher after 52 weeks at refrigerated storage, whereas 10 6 CFU/g were maintained at room temperature. This study favors air over nitrogen-based spray drying and confirms the method suitability for high viability retention over a year of shelf-life.